Anaerobic performance after 3-day consecutive CO2-rich cold-water immersion in physically active males - Mako Fujita (Journal of Exercise Science & Fitness, 2022)
Background/Objectives: We investigated the effects of a 3-day consecutive CO2-rich cold (20 °C) water immersion (CCWI) following a high-intensity intermittent test (HIIT) on subjects' sublingual temperature (Tsub), blood lactate ([La]b), and heart rate (HR) compared to cold (20 °C) tap-water immersion (CWI) or passive recovery (PAS). Methods: Thirty-two subjects were randomly allocated into three groups (CCWI, CWI, and PAS), each of which completed 4 consecutive days of cycling experiments. HR, Tsub, and [La]b were recorded on each day of exercise testing (immersion from Day 1 to Day 3 and Day 4). HIIT consisted of 8 sets of 20-sec maximum exercise at an intensity of 120% of VO2max with 10-sec passive rest. The mean and peak power, and peak pedal repetitions (PPR) within HIIT were averaged and the decline in PPR (ΔPPR) from Day 1 to Day 4 was measured. Results: In CCWI and CWI, HR declined significantly following each immersion, with CCWI showing the larger reduction (p < 0.001). At Day 2, CCWI showed a significantly lower [La]b compared to PAS (p < 0.01). The changes in mean and peak power from Day 1 to Day 4 did not differ among the groups (p = 0.302). ΔPPR of HIIT was significantly correlated with the HR and [La]b values after immersions (ΔPPR-HR: r2 = 0.938, p < 0.001, ΔPPR-[La]b: r2 = 0.999, p < 0.001). Conclusions: These findings indicate that CCWI is a promising intervention for maintaining peak performance in high-intensity intermittent exercise, which is associated with a reduction in [La]b and HR.